Effectiveness of distributed tuned mass dampers for multi-mode control of chimney under earthquakes. (1st October 2016) - Elias, Said; Matsagar, Vasant; Datta, T.K.
Highlights: Effectiveness of distributed tuned mass dampers (d-TMDs) for multi-mode seismic response control of geometrically regular and irregular chimneys is presented under un-cracked and cracked conditions. It is observed that the d-TMDs are more effective than the single tuned mass damper (STMD). The maximum reduction of about 35% in peak displacement at the topmost node is achieved for three d-TMDs. It is concluded that the positioning of the TMDs has a significant effect on the vibration response control. Abstract: Effectiveness of distributed tuned mass dampers (d-TMDs) designed according to the mode shapes for multi-mode control of chimneys as against the TMDs placed arbitrarily (ad-TMDs) and single TMD (STMD) under earthquake ground motions is investigated. The investigation includes geometrically regular and irregular chimneys under un-cracked and cracked conditions. A reinforced concrete (RC) chimney is considered as an assemblage of beam elements, each assumed to have constant diameter over the element length. The coupled differential equations of motion for the chimney and TMDs are derived and solved using Newmark's integration method. Best possible locations of the TMDs are identified based on the mode shapes of the uncontrolled (NC) chimney. A TMD is placed where the mode shape amplitude of the chimney is the largest or larger in a particular mode and is tuned with the corresponding modal frequency. The number of modes to be controlled is decided according to total modal mass participation being ninety percent. In order to achieve the objective of the study, the performance of the d-TMDs used in the present method is compared with the STMD and ad-TMDs cases. A parametric study is conducted to find the most suitable mass ratio and damping ratio for all cases. It is observed that the d-TMDs are more effective than the STMD and ad-TMDs for the same total mass of the TMD/TMDs.